Time series analysis of incidence of dengue and Aedes aegypti in Ceará - Estelita Pereira Lima; Marília Oliveira Fonseca Goulart; Mário Ronaldo Albuquerque; Fernanda Moura Victor; Natália Bitu Pinto (Universidade de Fortaleza, 2014)
Objective: To analyze the epidemiological behavior of dengue in the state of Ceara and the control of Aedes aegypti. Methods: This is a documentary study that used as data source the epidemiological bulletins published by the Ceara State Department of Health and other complementary documents from 1986 to 2011. A descriptive analysis of the incidence of dengue in this period was carried out according to age, severe forms, deaths and circulation of DEN-V virus. The study analyzed the vector control program and the evolution of infestation and dengue transmission in the same period. Results: It was found that, from 1986 to 2011, Ceara had five dengue epidemics with high incidence rates, and from 2008 to 2010, children were the most affected group. On average, there was Aedes aegypti infestation in 120 municipalities and transmission in 84 of them annually. The circulation of more than one serotype resulted in a large number of deaths almost every year, more than that estimated by the World Health Organization. Conclusion: The epidemiological behavior of dengue in Ceara justifies the classification made by the Ministry of Health that acknowledges the State as a Very High Risk-area with vulnerability to the disease. In recent years, the rate of severe cases has increased, probably because of the simultaneous circulation of three serotypes and the population's sensitization due to previous infections. This situation is aggravated by the vector presence in nearly the entire State and a deficient vector control policy. doi:10.5020/18061230.2013.p340